The Effect of Performance Benefits and Employee Engagement on Work Discipline with Job Satisfaction as a Mediator Variable (Study on Employee XXX) - Ferry Febriansyah Lubis; Maman Suratman (Syntax Literate, 2025)
Human resource development is the most important component, especially in terms of work discipline. The purpose of the study is to determine and analyse how the Effect of Performance Allowances and Employee Engagement on Work Discipline with Job Satisfaction as a Mediator Variable (Study on Employees of the XXX). This study observes and analyses using a descriptive quantitative approach which is defined as a tool to describe the situation and condition of their facts and symptoms obtained while the analytical tool used is using partial least square. The population in this study were 51 employees at the West Java Regional Staffing Agency. The research sample is part of the generalisation area, so the samples taken are all using purposive sampling. The results of the study state that Work Allowance has a significant effect on Work Discipline, Employee Engagement has a significant effect on Work Discipline, Job Satisfaction has a significant effect on Work Discipline, Work Allowance has a significant effect on Employee Engagement, There is a mediating effect of Job Satisfaction in the relationship of Work Allowance to Work Discipline, There is a mediating effect of Job Satisfaction in the relationship of Employee Engagement. on Work Discipline.